The Effectiveness of Using Two Stay Two Stray to Improve Students’ Speaking Skills - Mariska, Refi; Ferdiyanto, Feri; Hamdani, Beny (Journal of English Language and Education, 2025)
This study aims to investigate the effectiveness of the Two Stay Two Stray (TSTS) technique in improving students’ speaking skills at junior high school. The background of this research is based on the fact that speaking is often the most challenging aspect of English language learning, as students tend to fear making mistakes and lack self-confidence. This research employed a quantitative approach with a quasi-experimental design involving an experimental group and a control group. The instruments used were speaking tests, observation, and documentation. Data analysis using the t-test revealed a significant difference between students taught using the TSTS technique and those who were not. The findings indicate that the TSTS technique is effective in enhancing students' speaking skills, as it promotes active interaction, idea exchange, and increased confidence. The implications of this study suggest that teachers are encouraged to integrate the TSTS technique in speaking instruction to create a more communicative and participatory learning environment.